Function utilization on Computer Components - Fitria Claudya Lahinta; Jusuf Luther Mappadang; Ridho Modeong; Rizki Cahyadi; Resky Awalia Baharani; Jherodicse Jaesu Cleverino Mananentung (Jurnal Syntax Admiration, 2025)
This paper describes the utilization of functions on the components of computer components that include all devices on the computer that have certain functions that are used to run programs and systems on the computer and make a complex unit so that it can be used as a tool that facilitates work such as creating documentation, site programs, and percentage data in accordance with the wishes of the user the purpose of making this paper as a means of increasing knowledge for students and students who are studying about the computer field. The computer itself is a tool used to facilitate its users in finding information or as a means of making documents or office data which includes research data, observation data, thesis data, and many more. In addition, computers have been used more than decades ago which have been used by progamers to create a site that until now has been worldwide until now it has been widely used by many people in the world not only that computers have also undergone development from the beginning of manufacture to the present so that many components in computers have changed their physical form and use so that we are important to know the function of each component of the computer components so we have to learn about computer components.